Proceedings of a British Nuclear Energy Society conference at the University of Reading on 25 and 26 September 1974 - Pugh, S. F. 1922- (British Nuclear Energy Society, 1975)
These are the proceedings for the conference organised by the British Nuclear Energy Society, with papers reviewing the status of Alloy 800, and Chromium-Iron-Nickel alloy.